Effectiveness of some β- lactamase encoding genes on biofilm formation and slime layer production by uropathogenic Escherichia coli - Najlaa N. Yaseen; Al-Mathkhury, Harith J. F. (World Journal of Experimental Biosciences, 2015)
In present study 74 specimens of urine were collected from patients suffering from urinary tract infections. Fifty (67.56%) isolates were identified as Escherichia coli. 78% of isolates were identified as extended spectrum beta-lactamases (ESBL) producer. Antibiotic susceptibility test was done and ceftazidime was selected to complete this study by implying stress at sub-MIC on isolate harbor high number of resistance genes (N11) and compared with sensitive isolate (S). Only four β-lactamase coding genes were detected; blaTEM, blaPER, blaVIM and blaCTX-M-2, and N11 had blaTEM, blaPER, and blaVIM. It was found that the resistant isolate did not form biofilm when compared with the sensitive one, which formed moderate biofilm. In addition, ceftazidime stress reduced the ability to produce slime layer and affected the viable bacterial count in combination with pH and temperature stresses.
Keywords: Uropathogenic E. coli, β-lactamase, Biofilm., Slime layer.